Recovering Images from PET Camera - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
We study here one of the imaging techniques, used in nuclear medicine, called positron emission tomographic imaging, that provides information about many biological processes that are essential to the functioning of the organ, being visualized. Our emphasis is given to the application of the maximum entropy image reconstruction method called Cambridge MaxEnt Package for recovering images of the human brain from data obtained by positron emission tomographic camera.
Keywords: TOMOGRAPHY; RECONSTRUCTION